Synthesis and anticoagulating potentials of chitosan nanoparticle from cuttlebone of Sepiella inermis (Orbingy, 1848) - G. Sasi Priya.; Yagniyasree Manogaran; Revathi Duraisamy; Dhanraj Ganapathy; Pasiyappazham Ramasamy (Next Nanotechnology, 2025)
This study explores the synthesis and evaluation of chitosan nanoparticles derived from the cuttlebone of Sepiella inermis, highlighting their anticoagulant potential. Chitin and chitosan were extracted from cuttlebone waste, and subsequent physical and chemical modifications led to the creation of chitosan nanoparticles. Advanced characterization methods such as FTIR, FESEM and XRD were employed, confirming the nanoparticles' structural integrity, chemical composition, and uniform morphology. In vitro anticoagulant activity was assessed through APTT and PT coagulation tests, revealing significantly prolonged clotting times compared to heparin, thus demonstrating their potent anticoagulant properties. The results indicate that these nanoparticles possess intrinsic anticoagulant capabilities, offering a promising alternative to conventional anticoagulants. Moreover, their biocompatible and biodegradable nature adds to their suitability for medical applications. The transformation of cuttlebone waste into valuable biomedical materials underscores the environmental benefits of this approach, aligning with sustainable practices in science and medicine. This research represents a significant step towards innovative and sustainable solutions in healthcare, promoting the development of next-generation therapeutic agents.